Detailed CO(J = 1–0, 2–1, and 3–2) observations toward an H ii region RCW 32 in the Vela Molecular Ridge. (26th March 2018) - Enokiya, Rei; Sano, Hidetoshi; Hayashi, Katsuhiro; Tachihara, Kengo; Torii, Kazufumi; Yamamoto, Hiroaki; Hattori, Yusuke; Hasegawa, Yutaka; Ohama, Akio; Kimura, Kimihiro; Ogawa, Hideo; Fukui, Yasuo
Abstract: We performed CO( J = 1–0, 2–1, and 3–2) observations toward an H ii region RCW 32 in the Vela Molecular Ridge. The CO gas distribution associated with the H ii region was revealed for the first time at a high resolution of 22″. The results revealed three distinct velocity components which show correspondence with the optical dark lanes and/or Hα distribution. Two of the components show complementary spatial distribution which suggests collisional interaction between them at a relative velocity of ∼ 4 km s −1 . Based on these results, we present a hypothesis that a cloud–cloud collision determined the cloud distribution and triggered formation of the exciting star ionizing RCW 32. The collision time scale is estimated from the cloud size and the velocity separation to be ∼2 Myr and the collision terminated ∼1 Myr ago, which is consistent with the age of the exciting star and the associated cluster. By combing the previous works on the H ii regions in the Vela Molecular Ridge, we argue that the majority (at least four) of the H ii regions in the Ridge were formed by triggering of cloud–cloud collision.